Developing group skills [videorecording] : teachers perspectives / Shelly Freeman - Freeman, Shelly author; Institute for Development of Education Activities (New York : Insight Media, 2005)
In a lecture given for the 23rd IDEA Fellows Program, Shelley Freeman explains that effective groups are predicated on a clear understanding of group behavior and dynamics. She teaches techniques for developing communication, group trust, conflict resolution, and decision making skills.